Dispositivo eletroquímico miniaturizado e microextração em gota única por headspace: uma combinação promissora para determinação de nitrito - Fernandes, Leticia Baldissera (2022)
Considering the wide applicability of nitrite in various sectors, from agriculture to industry and, mainly used in the food field as preservatives for beverages and processed foods, it is undeniable that the nitrite ion has contributed to the development of society; however, the discovery of its potential toxicity has raised numerous concerns and for this reason, the detection of nitrite is quite relevant for public health and environmental monitoring. In view of the above, the development of miniaturized devices made from reused materials combined with a microextraction technique, is a more environmentally friendly, accessible, and promising approach for nitrite quantification. This combination reuses materials for the construction of the electrochemical device, remarkably decreasing the total cost of the system, also reducing the amount of chemicals and sample consumed and residues produced, since the analyzes are performed on the μL volume scale, without the need for organic solvents in the extraction. In this sense, the purpose of this work was to employ a miniaturized electrochemical device made from alternative and reused materials combined with a headspace single drop microextraction step, also considered a miniaturized extraction technique. Through the results, it is evident that the combination of the device with the microextraction step improved the analytical performance of the device, decreasing the detection and quantification limits, in addition to substantially improving the sensitivity when compared to the results without the extraction step. These observed effects are justified due to the pre-concentration achieved, when only 500 μL of solution were used in the electroanalytical analyses. In addition, an advantage of the method is related to the fact that there was no need to modify the electrode surface, a step that, in most works, requires time-consuming synthetic methodologies and uses expensive reagents. Finally, the applicability of the system for quantification of nitrite was evaluated for different samples of water, tap, mineral and aquarium at different concentration levels (30, 60, 90 and 120 μmol L-1), obtaining recovery values close to 100%. In view of all the listed aspects, this work describes a promising analytical system for nitrite determination, making accessible and ecological methodologies to be increasingly explored.